2018
DOI: 10.1016/j.cmet.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Cancer Metabolic Signature Predicts Co-Dependency on Glutaminase and De Novo Glutathione Synthesis Linked to a High-Mesenchymal Cell State

Abstract: The enzyme glutaminase (GLS1) is currently in clinical trials for oncology, yet there are no clear diagnostic criteria to identify responders. The evaluation of 25 basal breast lines expressing GLS1, predominantly through its splice isoform GAC, demonstrated that only GLS1-dependent basal B lines required it for maintaining de novo glutathione synthesis in addition to mitochondrial bioenergetics. Drug sensitivity profiling of 407 tumor lines with GLS1 and gamma-glutamylcysteine synthetase (GCS) inhibitors reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 60 publications
2
64
0
Order By: Relevance
“…Notably, if GLS2 has location-specific functions independent of glutaminolysis in cell nuclei, it could become a promising target. Actually, the pattern of GLS and GLS2 expression differentially modulate the clinical outcome of cancers 55 and is becoming a useful metabolic signature to diagnose responders to GLS cancer therapy 56,57 .…”
Section: Scientific Reports |mentioning
confidence: 99%
“…Notably, if GLS2 has location-specific functions independent of glutaminolysis in cell nuclei, it could become a promising target. Actually, the pattern of GLS and GLS2 expression differentially modulate the clinical outcome of cancers 55 and is becoming a useful metabolic signature to diagnose responders to GLS cancer therapy 56,57 .…”
Section: Scientific Reports |mentioning
confidence: 99%
“…Surprisingly, our pharmacometabolic studies revealed that C968 treatment neither increased intracellular Gln, nor did it reduce the concentrations of Glu, Glu-dependent amino acids (Ala, Asp) or the TCA cycle intermediate Suc (Fig. 5), all validated metabolic indicators for successful GLS suppression 51,57,60 . This suggests that the phenotypes observed upon C968 treatment (Figs.…”
Section: Discussionmentioning
confidence: 79%
“…3, A and C). Notably, the up-regulation of GLS was confined to the spliced isoform glutaminase C (GLS-GAC) (approximately 4.5-fold change Mfn2cKO/CTRL, P = 0.05), whose specific up-regulation is observed in cancer tissue to support mitochondrial bioenergetics (27). The fact that BCAA catabolism emerged as one of the key up-regulated pathways in our analysis strongly suggests that the anaplerotic flux into the TCA cycle may be altered in OXPHOSdeficient PNs.…”
Section: Mitochondrial Dysfunction In Neurons Induces Tca Cycle Anaplmentioning
confidence: 99%